2021
DOI: 10.1093/schizbullopen/sgab009
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Psychiatric Service Use and Mortality by Migrant Status Following a First Diagnosis of Psychotic Disorder: A Swedish Cohort Study of 1.3M People

Abstract: It is unclear whether inequalities in mental healthcare and mortality following the onset of psychosis exist by migrant status and region-of-origin. We investigated whether (i) mortality (including by major causes of death); (ii) admission type (in- or out-patient), and; (iii) in-patient length of stay at first diagnosis for psychotic disorder presentation, and; (iv) time-to-readmission for psychotic disorder differed for refugees, non-refugee migrants and by region-of-origin. We established a cohort of 1,335,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Our findings are consistent with those of previous studies that have observed an increased risk of hospitalization among nonrefugee migrants and refugees 14 , 15 and with Swedish studies showing that the risk is even greater among those who had more recently migrated and individuals who had migrated from Africa. 12 , 14 Importantly, we extended these findings by showing this was also true of second-generation migrants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with those of previous studies that have observed an increased risk of hospitalization among nonrefugee migrants and refugees 14 , 15 and with Swedish studies showing that the risk is even greater among those who had more recently migrated and individuals who had migrated from Africa. 12 , 14 Importantly, we extended these findings by showing this was also true of second-generation migrants.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of previous studies that have observed an increased risk of hospitalization among nonrefugee migrants and refugees 14 , 15 and with Swedish studies showing that the risk is even greater among those who had more recently migrated and individuals who had migrated from Africa. 12 , 14 Importantly, we extended these findings by showing this was also true of second-generation migrants. Migrant status has been associated with delays in help seeking and a longer DUP, 31 , 32 potentially due to a lack of awareness or understanding of local service provision, language barriers, and stigma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 After psychosis onset, migrant groups tend to face greater difficulties accessing mental health care, as evidenced by more negative and coercive pathways to care, [3][4][5] lack of timely follow-up after first diagnosis, 6,7 and longer duration of untreated psychosis. 8,9 Once treatment is initiated, migrant groups are at a greater risk of rehospitalization and involuntary admission, 5,[10][11][12] nonadherence to antipsychotic medications 13,14 and disengagement from services, 12,15 which may have consequences for long-term outcomes, particularly for people who migrate in the context of adversity. 16 The reasons underlying these observed disparities in service use and clinical outcomes for migrant groups with psychotic disorders are likely complex and remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%